Candidate Ap stars in close binary systems. Issue Volume 9:Issue S302(2013) (7th August 2014) - Folsom, C. P.; Wade, G. A.; Likuski, K.; Kochukhov, O.; Alecian, E.; Shulyak, D.; Johnson, N. M.
Abstract: Short period binary systems containing magnetic Ap stars are anomalously rare. This apparent anomaly may provide insight into the origin of the magnetic fields in theses stars. As an early investigation of this, we observed three close binary systems that have been proposed to host Ap stars. Two of these systems (HD 22128 and HD 56495) we find contain Am stars, but not Ap stars. However, for one system (HD 98088) we find the primary is indeed an Ap star, while the secondary is an Am star. Additionally, the Ap star is tidally locked to the secondary, and the predominately dipolar magnetic field of the Ap star is roughly aligned with the secondary. Further investigations of HD 98088 are planned by the BinaMIcS collaboration.